Toxicity of fipronil insecticide on the early life stages of Colossoma macropomum (gamitana) - Espinoza Morriberón, Dante (2021)
The present study was aimed to determine the lethality of the insecticide fipronil on two early life stages, post-larvae, and fingerling, of Colossoma macropomum, by determining the lethal concentration 50 (LC50). Five nominal concentrations (0.12; 0.165; 0.21; 0.255 and 0.30 mg/L) and a control in 4 replicates per treatment for 48 hours of exposure were used for the post-larvae; and other nominal concentrations (0.22; 0.27; 0.34; 0.43 and 0.54 mg/L) and a control in 3 replicates per treatment for 96 hours of exposure were used for the fingerling stage. The LC50 value was calculated as 0.22 mg/L and 0.33 mg/L for the post-larvae and fingerling stages, respectively. In addition, the maximum concentration that causes no mortality (MCNM) and the minimum concentration that causes mortality (MCM) for the post-larvae stage were determined as 0.12 and 0.15 mg/L, respectively; and 0.16 and 0.22 mg/L for the fingerling stage, respectively. C. macropomum showed erratic swimming, spasms in the region of the peduncle, caudal fin, and accelerated opercular movement in both life stages. The LC50 values calculated in the present study are considered “highly toxic” for the early stages of life of this non-target organism, suggesting that C. macropomum may be a sensitive species to fipronil insecticide.